EDUKASI PANDUAN MINUM OBAT BAGI PENDERITA PENYAKIT DIABETES SAAT BERPUASA - Susanty, Adriani; Fernando, Armon; Octavia, Rickha; Arief, Encik Juliansyah; Putri, Dhini Fahira; Safitri, Fasri Dian; Aprilia, Indri; Syafutri, Lidiyah; Aulia, Nada Aqilah; Farisa, Nayla Al; Jannati, Nisa; Ramona, Paula; Mayrade, Salma Yudhistira (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Diabetes mellitus is a chronic disease that poses challenges during Ramadan fasting due to changes in dietary patterns and mediacation schedules. These conditions may increase the risk of hypoglycemia and hyperglycemia, thus requiring proper health education. This community service aimed to improve diabetic patients knowledge regarding medication use during fasting. The methods included lectures, distribution of leaflets, and evaluation using pre-test and post-test questionnaires. The activity was carried out at Raudhatul Jannah Mosque Pekanbaru, on March 16, 2025, involving 30 participants. The results showed an improvement in participants knowledge, where the “very good” category increased from 13,3% to 40% after the intervention, Statistical analysis using a T-test obtained a p-value of 0,014 indicating a significant difference. This program demonstrated that simple education through counseling and leaflet distribution is effective in enhancing public understanding of proper medication use for diabetic patients during fasting.